Numerical methods for fractional calculus - Li, Changbin; Zeng, Fanhai (Chapman & Hall/CRC numerical analysis and scientific computing, 2015)
Numerical Methods for Fractional Calculus presents numerical methods for fractional integrals and fractional derivatives, finite difference methods for fractional ordinary differential equations (FODEs) and fractional partial differential equations (FPDEs), and finite element methods for FPDEs.